Clinical relevance of serum electrolytes in dogs and cats with acute heart failure: A retrospective study. (7th June 2021) - Roche‐Catholy, Marine; Van Cappellen, Iris; Locquet, Laurent; Broeckx, Bart J. G.; Paepe, Dominique; Smets, Pascale
Abstract: Background: Hypochloremia is a strong negative prognostic factor in humans with congestive heart failure (CHF), but the implications of electrolyte abnormalities in small animals with acute CHF are unclear. Objectives: To document electrolyte abnormalities present upon admission of small animals with acute CHF, and to assess the relationship between electrolyte concentrations and diuretic dose, duration of hospitalization and survival time. Animals: Forty‐six dogs and 34 cats with first onset of acute CHF. Methods: Retrospective study. The associations between electrolyte concentrations and diuretic doses were evaluated with Spearman rank correlation coefficients. Relationship with duration of hospitalization and survival were assessed by simple linear regression and Cox proportional hazard regression, respectively. Results: The most commonly encountered electrolyte anomaly was hypochloremia observed in 24% (9/46 dogs and 10/34 cats) of cases. In dogs only, a significant negative correlation was identified between serum chloride concentrations at admission (median 113 mmol/L [97‐125]) and furosemide doses both at discharge (median 5.2 mg/kg/day [1.72‐9.57]; r  = −0.59; P  < .001) and at end‐stage heart failure (median 4.7 mg/kg/day [2.02‐7.28]; r  = −0.62; P  = .005). No significant hazard ratios were found for duration of hospitalization nor survival time for any of the electrolyte concentrations. Conclusions and Clinical Importance: The observed association between serum chloride concentrations and diuretic doses suggests that hypochloremia could serve as a marker of disease severity and therapeutic response in dogs with acute CHF.